PEMANFAATAN PUPUK KASCING UNTUK MENINGKATKAN PRODUKSI TANAMAN HORTIKULTURA - Damaita, Iz; Mustikarini, Eries Dyah; Khodijah, Nyayu Siti (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Horticultural crops are plants that are very important for food production. This plant makes a significant contribution to food supply, nutrition and the global economy. The aim of this Scientific Journal is to analyze the use of vermicompost fertilizer and its contents in horticultural crop production. This Scientific Journal was prepared using a descriptive method, namely by conducting a literature study consisting of reviewing various literature using the literature study method and drawing conclusions. Horticultural plants can be cultivated by providing various types of fertilizer and with the right dosage, one of which is organic vermicompost fertilizer which contains organic N, P and C which is good for Teruma plants to support the vegetative period and enter the production period. Vermicompost fertilizer has also been tested with various types of horticultural plants such as mustard greens, eggplant, cabbage and others. The combination of vermicompost and NPK fertilizer gave maximum results on fruit weight and number of fruit on eggplant plants compared to other organic fertilizers, for fresh weight of Pakcoy mustard greens while the effect of vermicompost and NPK fertilizer showed maximum results. Treatment of vermicompost and NPK fertilizer. Vermicompost and NPK fertilizers which provide maximum results are a harvest index of 1.45 which is produced when compared with treatments of manure, Za, Urea and also Kayabio biological fertilizer.